Upaya Meningkatkan Kepuasan Kerja Melalui Pengembangan Karir Dan Kepemimpinan Pada PT. Traglopindo Utama - Ahmad Rivai (MTU PRESS, 2022)
Employees are assets for the company in realizing the company's targets. Job satisfaction makes it easier for a leader to direct his subordinates. The purpose of this study is to analyze the effect of both simultaneously and partially career development and leadership variables on job satisfaction at PT. Main Traglopindo. The approach in this research is associative. The population in this study are employees at PT. Traglopindo Utama totaled 73 respondents. While the sampling technique using quota sampling. Collecting data using a questionnaire with a Likert scale. The results showed that simultaneously career development and leadership had a positive and significant effect on job satisfaction at PT. Main Traglopindo.